Finite Difference Method for an Optimal Control Problem for a Nonlinear Time-dependent Schrödinger Equation. (3rd June 2017) - Yıldırım Aksoy, Nigar; Hào, Dinh Nho; Yagub, Gabil
ABSTRACT: The finite difference method is applied to an optimal control problem for a system governed by a nonlinear Schrödinger equation with a complex coeﬃcient. The optimal control problem is discretized by the finite difference method, the error estimate for the finite difference scheme is established and the convergence of difference approximations of the optimal control according to the functional is proved.